Impact of carboxylesterase 1 genetic polymorphism on trandolapril activation in human liver and the pharmacokinetics and pharmacodynamics in healthy volunteers - Xinwen Wang; Lucy Her; Jingcheng Xiao; Jian Shi; Audrey H. Wu; Barry E. Bleske; Hao‐Jie Zhu (Wiley, 2021)
Abstract Trandolapril, an angiotensin‐converting enzyme inhibitor prodrug, needs to be activated by carboxylesterase 1 (CES1) in the liver to exert its intended therapeutic effect. A previous in vitro study demonstrated that the CES1 genetic variant G143E (rs71647871) abolished CES1‐mediated trandolapril activation in cells transfected with the variant. This study aimed to determine the effect of the G143E variant on trandolapril activation in human livers and the pharmacokinetics (PKs) and pharmacodynamics (PDs) in human subjects. We performed an in vitro incubation study to assess trandolapril activation in human livers (5 G143E heterozygotes and 97 noncarriers) and conducted a single‐dose (1 mg) PK and PD study of trandolapril in healthy volunteers (8 G143E heterozygotes and 11 noncarriers). The incubation study revealed that the mean trandolapril activation rate in G143E heterozygous livers was 42% of those not carrying the variant (p = 0.0015). The clinical study showed that, relative to noncarriers, G143E carriers exhibited 20% and 15% decreases, respectively, in the peak concentration (Cmax) and area under the curve from 0 to 72 h (AUC0-72 h) of the active metabolite trandolaprilat, although the differences were not statistically significant. Additionally, the average maximum reductions of systolic blood pressure and diastolic blood pressure in carriers were ~ 22% and 23% less than in noncarriers, respectively, but the differences did not reach a statistically significant level. In summary, the CES1 G143E variant markedly impaired trandolapril activation in the human liver under the in vitro incubation conditions; however, this variant had only a modest impact on the PK and PD of trandolapril in healthy human subjects.